Nutrients in folate-mediated, one-carbon metabolism and the risk of rectal tumors in men and women - Curtin, Karen; Samowitz, Wade S.; Ulrich, Cornelia; Wolff, Roger K.; Herrick, Jennifer S.; Caan, Bette J.; Slattery, Martha L. (Nutrition and cancer, 2011)
In an investigation of rectal tumors characterized by CpG island methylator phenotype (CIMP), KRAS2 mutation, and TP53 mutation, we examined associations with dietary and supplemental folate, riboflavin, vitamins B6 and B12, and methionine, nutrients involved in folate-mediated 1-carbon metabolism. We also examined folate intake and common MTHFR polymorphisms in relation to CIMP. Data from a population-based study of 951 cases (750 with tumor markers) and 1,205 controls were evaluated using multiple logistic regression models and generalized estimating equations. Reduced risk of methylated tumors was suggested in women with the upper tertile of folate intake (≥0.42 mg/day) vs. the lower tertile: OR = 0.6, 95%CI = 0.3-1.2. In men, a significant 3-fold increased risk of CIMP+ tumor was observed for the upper tertile of folate (≥0.75 mg/day) vs. the lower tertile (<0.44 mg/day): OR = 3.2, 95%CI = 1.5-6.7. These men consumed a greater proportion of folic acid fortified foods relative to natural, primarily plant-based sources (52% vs. 48%) than women with CIMP+ tumors (22% vs. 78%). MTHFR 1298A>C influenced folate in male CIMP+ risk (P interaction < 0.01). Our findings suggest folate supplementation effects may differ between genders, perhaps due to variation in MTHFR and/or endogenous/exogenous hormones, and may be important in the initiation and progression of methylated rectal tumors in men.
Gesehen am 22.04.2022